WAYANG ORANG PERKU M PU LAN MASYARAKAT SURAKARTA (PMS) EKSPRESI ETNIS CINA MENJAWA - Nora Kustantina Dewi (Gelar : Jurnal Seni Budaya, 2006)
Wayang orang or Javanese Stage Show has been spread out from the palace since the socio-structural changing in Javanese community in the end of 1.91' century, This circumstances brought to the influences of the development of wayang orang out side of Pura Mangkunegara Palace as a commercial art performance. In 1958, the members of People Community of Surakarta/ Perkumpulan Masyarakat Surakarta (PMS) built a group of wayang orang, which the players and the pang rawit/traditional music player 90% were the Chinese ethnic. Wayang Orang PMS has growth in acculturation process of _Javanese and Chinese Culture, which were completing each other in the successful of its arts work. Wayang orang has become the one of the way to express in Chinese ethnic mix in the melting pot of the beautifulness of the arts work. People Community of Surakarta as the place of socio cultural interaction includes its wayang orang, still exists and actives in the understanding of the state unity, assimilation in any natural and individual process.Key words: Chinese Ethnic 'Wayang Orang' to be likes Java